Exploring sport participants' event and destination choices. Issue 2 (3rd April 2018) - Newland, Brianna L.; Aicher, Thomas J.
ABSTRACT: This study explored the relationship between destination and event elements and an individual's motivation to travel for sport events. Investigators surveyed participants who were planning to travel or had recently travelled to at least one running, cycling, or triathlon event in the current competitive race season. Data were analysed using exploratory factor analysis, regression, cross-tabulation, and ANOVA. The findings provide empirical evidence that travel behaviours vary by athlete type (runner, triathlete, and cyclist). The results of this study not only add to the push/pull theoretical framework but also provide strong practical implications for both event managers and destination marketers to better package destination attributes and event elements specific to athlete type.